2022
DOI: 10.3390/fire5050169
|View full text |Cite
|
Sign up to set email alerts
|

Fire and Herbivory Interactively Suppress the Survival and Growth of Trees in an African Semiarid Savanna

Abstract: There has been a long-standing interest in understanding how interactions between fire and herbivory influence woody vegetation dynamics in savanna ecosystems. However, controlled, replicated experiments examining how different fire regimes interact with different herbivore groups are rare. We tested the effects of single and repeated burns, crossed with six replicated herbivore treatments, on the mortality and growth of woody vegetation in the Kenya Long-term Exclosure Experiment plots located in a semi-arid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The most probable reason for this is the low fuel load in the treatments, due to herbivory, leading to a low fire intensity, which is described in Paper III. Similar results were also found in a study by Ngugi et al (2022) in Kenya, where the amount of fuel was reduced by the cattle to the level where fire had no longer an effect on tree establishment and recruitment.…”
Section: Fire and Herbivory Suppress Tree Recruitment And Promote Gra...supporting
confidence: 87%
See 1 more Smart Citation
“…The most probable reason for this is the low fuel load in the treatments, due to herbivory, leading to a low fire intensity, which is described in Paper III. Similar results were also found in a study by Ngugi et al (2022) in Kenya, where the amount of fuel was reduced by the cattle to the level where fire had no longer an effect on tree establishment and recruitment.…”
Section: Fire and Herbivory Suppress Tree Recruitment And Promote Gra...supporting
confidence: 87%
“…In a study from the African savanna, native ungulates prevented woody expansion and Capozzelli et al (2020) showed that introducing both fire and herbivory into the landscape decreased the woody encroachment on grasslands in central North America. Similar results were found in studies in the African savanna (Ngugi et al, 2022;. All of these studies show that fire and herbivores are important factors that can control woody vegetation.…”
Section: Introduction 11 Open Ecosystemssupporting
confidence: 87%
“…2005;Nzunda et al 2008). Even though re had a greater negative effect on resprouting vigour than browsing, the impacts of continuous browsing or sustained browsing of young post-re resprouts may have a greater negative impact on resprouting vigour than just re, whereby stored carbohydrate reserves become depleted(Schutz et al 2011;Ngugi et al 2022), but this is yet to be investigated for thicket shrubs.Pre-treatment shrub size had a strong positive in uence on survival and resprouting vigour after both defoliation treatments. This is unsurprising since larger plants can mobilize more carbohydrates post disturbance(Vesk 2006; Lawes et al 2011; Marais et al 2014; Strydom et al 2020;Staver et al 2009).…”
mentioning
confidence: 99%
“…2016; LaMalfa et al. 2019; Ngugi et al., 2022). We therefore have a limited understanding of the interacting effects of fire and LMH on savanna biodiversity and functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of top-down and bottom-up effects of fire and herbivores have quantified plant diversity, plant adaptations to fire and herbivory (Bond & Midgley, 2001;Bond & Keeley, 2005;Charles-Dominique et al, 2015), nutrient cycling (Coetsee et al, 2008;Coetsee et al, 2011;Holdo & Mack, 2014;Hempson, Archibald, Bond, Ellis, et al, 2015;Pellegrini et al, 2015), and changes in plant defenses (Chinder et al, 2020;Scogings et al, 2017). However, less attention has been paid to the influence of fire and herbivory on biodiversity broadly, and there are few fully factorial studies that evaluate the interactions between fire and large mammal herbivores (LMH; Levick et al, 2009;Burkepile et al 2016;LaMalfa et al 2019;Ngugi et al, 2022). We therefore have a limited understanding of the interacting effects of fire and LMH on savanna biodiversity and functioning.…”
Section: Introductionmentioning
confidence: 99%